Influence of different application protocols of universal adhesive system on the clinical behavior of Class I and II restorations of composite resin - a randomized and double-blind controlled clinical trial - Andreia Assis Carvalho; Murillo Martins Leite; Jessica Karla Maia Zago; Carla Aparecida Bernardes Costa Meneses Nunes; Terezinha de Jesus Esteves Barata; Gersinei Carlos de Freitas; Érica Miranda de Torres; Lawrence Gonzaga Lopes (BMC, 2019)
Abstract Background Multimode adhesives incorporate the versatility of adapting to various clinical situations by its capacity to be used in different protocols. This study aimed to evaluate the clinical behavior of composite resin direct restorations (Class I and II) performed with different universal dentin adhesive application protocols comparing adapted FDI and adapted USPHS criteria. Methods The current study is a randomized, double-blind, split-mouth, and convenience sample controlled clinical trial. The participants (age ≥ 18 years) had restorative need of Class I and/or II due to the presence of carious lesions and/or unsatisfactory restorations in at least three dental elements. Each participant received three application protocols for Scotchbond Universal adhesive (3M ESPE), one in each tooth to be restored: ER = etch-and-rinse + adhesive (n = 50); SEE = selective enamel etch + adhesive (n = 50) and SE = self-etch adhesive (n = 50). All teeth were restored in a similar way using Filtek™ Supreme composite resin (3M ESPE). Restorations were evaluated using the adapted FDI and adapted USPHS criteria, at baseline after 7 to 21 (12.02 ± 5.68) days (T1; n = 50 per group) and after 12 to 20 (15.8 ± 2.7) months (T2; n = 46 per group) by two previously calibrated evaluators (Kappa > 0.80). The statistical tests were performed between groups (Friedman), intragroup (Wilcoxon), and between the criteria considering acceptable and not acceptable restorations (McNemar), α = 0.05. Results A statistically significant difference was observed only for the property "superficial staining", between groups at T2 (p = 0.01) for ER (n = 13 with score 2 or more) and SEE (n = 3 with score 2 or more) and intragroup for ER (T1, n = 1 with score 2 or more; T2, n = 13 with score 2 or more, p = 0.001) and SE (T1, n = 0 with score 2 or more; T2, n = 8 with score 2 or more p = 0.007). For the other comparisons between groups, intragroup, and between the adapted FDI and adapted USPHS criteria, there were no statistically significant differences (p ≥ 0.05). Conclusions It can be concluded that the different application protocols of the universal adhesive resulted in clinically "acceptable" restorations after 15.8 ± 2.7 months of follow-up. Adapted FDI and adapted USPHS criteria provided similar results to each other. Trial registration. Number in Brazilian Registry of Clinical Trials (ReBEC): RBR-9p3hdp. Registered 24 May 2015.